2018
DOI: 10.1038/s41396-018-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Bdellovibrio bacteriovorus HD100, a predator of Gram-negative bacteria, benefits energetically from Staphylococcus aureus biofilms without predation

Abstract: Bdellovibrio bacteriovorus HD100 is a predatory bacterium which lives by invading the periplasm of Gram-negative bacteria and consuming them from within. Although B. bacteriovorus HD100 attacks only Gram-negative bacterial strains, our work here shows attack-phase predatory cells also benefit from interacting with Gram-positive biofilms. Using Staphylococcus aureus biofilms, we show this predator degrades the biofilm matrix, obtains nutrients and uses these to produce and secrete proteolytic enzymes to continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 21 publications
2
45
0
Order By: Relevance
“…Bdellovibrio bacteriovorus is a small (0.2- to 0.5-μm wide and 0.5- to 2.5-μm long) Gram-negative bacterium that is unusual in its ability to invade and kill other Gram-negative bacteria. Moreover, it was demonstrated that B. bacteriovorus also benefits from interacting with Gram-positive biofilms ( Staphylococcus aureus ) (1). Bacteria belonging to the Bdellovibrio genus are largely found in wet, aerobic environments (i.e., soil) (2).…”
Section: Introductionmentioning
confidence: 99%
“…Bdellovibrio bacteriovorus is a small (0.2- to 0.5-μm wide and 0.5- to 2.5-μm long) Gram-negative bacterium that is unusual in its ability to invade and kill other Gram-negative bacteria. Moreover, it was demonstrated that B. bacteriovorus also benefits from interacting with Gram-positive biofilms ( Staphylococcus aureus ) (1). Bacteria belonging to the Bdellovibrio genus are largely found in wet, aerobic environments (i.e., soil) (2).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms represent a lump of prey for Bdellovibrio. It possesses the lytic enzymes needed to chew the extracellular matrix that holds cells within the biofilm and can likely derive valuable nutrients from this (Im et al 2018). Bdellovibrio can predate the metabolically inactive cells found deeper within biofilms and its gliding motility allows it to move within the biofilm (Lambert et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1B), suggesting the predatory activities might be enhanced under these conditions. To test this, we employed a bioluminescent strain of E. coli MG1655/pUCDK as the prey and measured the attack rates using the bioluminescence (BL) decrease (i.e., 'shutting-off') as described previously (Im et al, 2014;Im et al, 2018). The quantitative results for both the control and predated samples are provided in Fig.…”
Section: Enhanced Attack Rates Are Seen In Slightly Viscous Mediamentioning
confidence: 99%
“…The optical density of resuspended culture was adjusted to 1.0 (OD 600nm ) and the predator (top agar piece) was added to initiate predation. For the liquid predatory cultures, the typical PPR used was between 0.02 and 0.05, which was determined as described previously (Im et al, 2018). After predation overnight, the culture was filtered using a 0.45 μm filter (Advantec, USA) to remove any remaining prey or bdelloplasts and used in the predation experiments as described below.…”
Section: Bacterial Strains and Their Growthmentioning
confidence: 99%